Phylogeny and taxonomy of powdery mildew fungi of Erysiphe sect. Uncinula on Carpinus species - Braun U. (2014)
A phylogenetic analysis of the Erysiphe with uncinuloid ascoma appendages (Erysiphe section Uncinula, Erysiphales, Ascomycota) on Carpinus spp. was done using sequences of the rDNA ITS regions and the D1/D2 domains of the 28S rDNA. These results, combined with morphological data, revealed a complex consisting of several distinct taxa. These included the already described Erysiphe carpinicola on C. japonica distinguishable from the Erysiphe sp. on C. betulus and C. tschonoskii as well as the one on C. laxiflora. Thus, it was shown that Oidium carpini, described from Europe on Carpinus betulus, the powdery mildew with uncinula-like ascomata, recently found in Europe on this host, as well as an Erysiphe on C. tschonoskii in Japan, described previously as E. carpinicola, all belong to a single new species, named E. arcuata in this paper. As the powdery mildew on C. laxiflora was also distinct from other known species, it is named E. carpini-laxiflorae in this paper. The already described E. pseudocarpinicola and Erysiphe sp. on Carpinus cordata are two additional taxa, which are morphologically and genetically distinguished from the other species of Erysiphe sect. Uncinula on Carpinus spp. © 2006 German Mycological Society and Springer.